How much land is available for sustainable palm oil?. (March 2021) - Tapia, John Frederick D.; Doliente, Stephen S.; Samsatli, Sheila
Highlights: Fuzzy GIS-based land suitability modelling to determine available lands for sustainable palm oil. Identified locations that will not cause deforestation, biodiversity loss and land use change emissions. Available land areas are fragmented so socially and economically challenging to develop. Policies should focus on yield improvement, over land expansion, and supporting smallholdings. Require plantation heterogeneity, conservation set-aside and no-access to vulnerable forests. Abstract: Current consumption of palm oil accounts for one third of the growing world demand for vegetable oil. Amidst the burgeoning industry, huge ecological costs have been accrued within just three decades due to the rapid oil palm expansion in many parts of the world. Many oil palm plantations are linked to deforestation, biodiversity losses, land use change emissions, among other ecological problems. Total replacement of palm oil could result in even greater adverse environmental consequences as alternative crops will require more land. To satisfy the growing demands in a sustainable manner, any new plantations must be located in environmentally-benign lands. This study identifies and quantifies the potentially available lands in Malaysia and Indonesia through a novel fuzzy GIS-based land suitability analysis. Three maps were generated: biophysically suitable land, based on optimal conditions for oil palm cultivation, excluding peatlands and existing protected areas; environmentally suitable land, further excluding forest cover; and potentially available land, further excluding existing plantations and other land uses. About 4.5 million hectares of available land for new plantations have been identified that could provide 1.3 million tonnes per year of sustainable palm oil. However, most of these areas are fragmented and scattered throughout the entire archipelago, which could pose economic and socio-political hurdles to developers of sustainable palm oil. With affordable and fairer certification schemes, sustainable oil palm plantations can be achieved by smallholders on these potentially available lands. Yield improvement and biodiversity restoration of existing plantations should be the focus through revitalised sustainable agriculture and strategic forest conservation policies, respectively. The maps provide valuable policy insights into the possibility of future sustainable oil palm plantations and a starting point for on-the-ground assessment and further verification.